Futebol e política no Brasil: bases de multinotabilidade e padrões de imbricação - COELHO, José Hailton Costa (2017)
This dissertation exposes the main results of a research developed in the scope of the Laboratory of Studies on Political and Cultural Elites (LEEPOC / UFMA) entitled "Football and Politics in Brazil: basis of multinotability and imbrications patterns. Inserted on a ongoing studies agenda in LEEPOC, about indifferentiation between social spheres and constitution of domains marked by the overlapping of logics and registers of action in the Brazilian power space, the research sought to apprehend how certain agents combine leadership in World of football (club presidency) and institutional politics (holding elective positions). In the same way, it sought to verify other inscriptions associated to these, such as professional, cultural and associative activities, seeking to characterize the basis of the multinontabilities by the agents.